PREVALENCE AND PREDICTORS OF HYPERTENSION: A CROSS SECTIONAL STUDY AMONG PEOPLE COMING TO A TERTIARY HEALTH CARE FACILTY IN GARHWAL-UTTARAKHAND. - Gupta, Sudhir Kumar; Dixit, Sumeet; Singh, Amit Kumar; Nagaonkar, Sashikant; Malik, Nidhi (Indian Journal of Community Health, 2012)
Research question: What is the knowledge, attitude and practice towards HIV/AIDS in a general population? Objectives: (1) To assess the knowledge about mode of transmission, treatment and prevention of HIV/AIDS. (2) To study the socio demographic pattern, myths and misconceptions. Study design: Community based cross sectional study. Setting: Chunampett Village, Tamilnadu. Duration: March to May 2007. Participants: 845 both males and females above the age of 18 years interviewed at home. Results: Population surveyed was 845, comprising of 482 (57.04%) males and 363 (42.96%) females. Most of them were Hindus (96.10%). Main occupation was agriculture (39.41%) among males and house wives (33.73%) among females. 40.35% respondents belonged to low socioeconomic status. Illiteracy rate was high especially among females (43%).Source of information about HIV/AIDS was mass media in about 85% of the population. Majority of individuals (58.5%) were not aware that the disease was contagious. An overwhelming majority (98.59%) were aware about the mode of transmission of HIV/AIDS through sexual route. However about 20% had myths regarding transmission of disease. 65% knew that HIV/AIDS is preventable, yet only 4% used condoms. A vast majority (60-65%) were not aware that treatment and PEP were available free of cost in government hospitals. A majority of about 54.22% were of the opinion that the diagnosis of HIV/AIDS should not be kept confidential. Conclusion: The awareness about HIV / AIDS is high among the study population but the implementation of preventive measures is low. The knowledge about availability of prophylactic and therapeutic measures against HIV / AIDS in Govt. hospitals is also low.